Entrepreneurial Marketing and its Role in Organizational Ambidexterity: An Analytical Study of the Opinions of a Sample of Members of the College Councils in a Number of Private Universities in the City of Erbil - أحمد عبدالواحد, نسيبه; محمد ولي, عبدال (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The general framework: The general framework of this study represents the research problem, which was identified by raising many questions about the nature of the impact and the relationship between [entrepreneurial marketing] as an independent variable, and [organizational ingenuity] as a dependent variable. Therefore, the hypothesis of the study was designed from which the study hypotheses emerged, and for the purpose of verifying the validity of the hypotheses, all hypotheses were subjected to statistical analyzes and numerous tests using the statistical analysis program (SPSS V.26). Arbitrators and statistical methods were used for the purpose of verifying the validity and reliability of the questionnaire, simple and multiple linear regression, as well as the correlation. Objective: The current study aimed to explore the reality of [entrepreneurial marketing and its role in organizational ingenuity]. It is an analytical study based on analyzing samples of members of college council’s views in a number of private universities in the city of Erbil. The entrepreneurial marketing (proactive orientation, risk management, creativity) represented the dimensions of the independent variable, while the organizational ingenuity (exploring opportunities, exploiting opportunities, flexible organizational structure) represented the dimensions of the dependent variable were. Methodology: The study followed the descriptive approach, in describing the main and sub-variables, as well as the analytical approach in analyzing the impact and relationships between the main variables and their dimensions adopted in the study. The study sample was represented by the private universities in the city of Erbil, to represent the community scientifically. Eight universities surveyed out of [10]. The number of respondents to fill out the questionnaire was (90) individuals. The valid forms for analysis amounted to (90) forms out of [100] distributed forms. Conclusions and Suggestions: The study reached a set of main conclusions, including the results of correlation analysis revealing the existence of positive and high-level moral relationships between entrepreneurial marketing and organizational ingenuity at the macro and micro levels. This proves the benefit of the universities covered in this study from identifying entrepreneurial marketing and its contribution to organizational ingenuity. In addition, according to what was found by the analysis indicators at the aggregate level, there is a positive and significant effect of the entrepreneurial marketing variable on organizational ingenuity. Furthermore, the regression results also indicated the presence of an effect for each of the dimensions of entrepreneurial marketing, respectively, in building organizational ingenuity. The study suggested a set of proposals, the most important of which is the necessity of investing the strong relationship between entrepreneurial marketing and organizational ingenuity and how to direct this relationship.